Adhesive composition, adhesive sheet, laminate, and display comprising that laminate
By using propionate-based copolymer adhesives of vinyl propionate and isotope alcohol propionate, the problem of unstable adhesion between aurora plate and liquid crystal cells in high temperature and high humidity environments is solved, and the stability and transparency are improved.
Patent Information
- Application Number
- JP2023175423
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-19
- Filing Date
- 2023-10-10
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2043-10-10
AI Technical Summary
The prior art is difficult to maintain stable adhesion between the auroral plate of a liquid crystal display and the liquid crystal cells in high temperature and high humidity environments, and problems such as bubble generation, auroral plate floating and light penetration are prone to occur.
Using a propionate-based copolymer containing vinyl propionate and isotope alcohol propionate, combined with an adhesive of isotope alcohol propionate, the low viscosity and high transparency of the adhesive are improved by adjusting the content of non-volatile ingredients and the formulation of the adhesive.
The stable adhesion between the aurora plate and liquid crystal cells in high temperature and high humidity environments is achieved, reducing the problem of reduced light penetration and floating, and maintaining high transparency and intensity.
Smart Images

Figure 2025044095000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a pressure-sensitive adhesive composition suitable for fixing a polarizing plate, a pressure-sensitive adhesive sheet, a laminate, and a display including the laminate. [Background technology]
[0002] Display devices such as liquid crystal displays used in various devices such as electronic calculators, electronic clocks, mobile phones, televisions, and other home and commercial electrical appliances are becoming larger, especially in liquid crystal and plasma televisions. In recent years, touch panel type liquid crystal displays, including those for smartphones and tablets, have rapidly spread, and the market is expected to expand significantly in the future. On the other hand, liquid crystal displays are also used in in-vehicle devices such as car navigation systems, and are required to be durable enough to be used in harsh in-vehicle environments such as high temperature and humidity. Liquid crystal displays use polarizing plates and retardation plates with various optical functions, and these are attached to adherends such as liquid crystal cells made of glass or transparent plastic via adhesives.
[0003] The polarizing plate is generally a laminate in which a polyvinyl alcohol film is sandwiched between a triacetyl cellulose film or a cycloolefin film, and these films have different mechanical properties and therefore different dimensional change rates when heated, so that when placed in a high-temperature atmosphere, the laminate often warps.
[0004] For example, when a liquid crystal cell member consisting of a polarizing plate / adhesive layer / glass (glass is a surface member of a liquid crystal cell) is left in a high-temperature atmosphere, problems such as warping due to the dimensional change rate between the constituent members of the polarizing plate, air bubbles (foaming) at the bonding interface between the adhesive layer and the glass, and the polarizing plate lifting off the glass may occur. In addition, the stress distribution of the liquid crystal cell member becomes non-uniform due to warping, and the stress is concentrated at the peripheral edge of the liquid crystal cell member, which may cause a problem of light leaking from the four corners and peripheral edge of the liquid crystal cell member, a so-called "light leakage phenomenon." The above problem also occurs in a high-temperature and high-humidity atmosphere.
[0005] On the other hand, in the manufacturing process of liquid crystal displays, etc., when a polarizing plate is attached to an optical component such as a liquid crystal cell, if there is a deviation in the attachment position, the polarizing plate is peeled off after a certain time has passed since attachment, and the expensive liquid crystal cell is reused. Therefore, the adhesive is required to have the property (reworkability) that allows the polarizing plate to be peeled off from the liquid crystal cell again after a certain time has passed since attachment.
[0006] In addition, in order to make it easier to coat when making adhesive sheets, adhesives are generally diluted and adjusted to a low viscosity before use. The solvent used for adjusting the viscosity is required to be as low in content as possible from the viewpoints of cost and handling. Furthermore, when the non-volatile content of the adjusted solution is low, it tends to be difficult to apply the adhesive thickly and uniformly, so there is a demand for low-viscosity adhesives that can have a higher non-volatile content.
[0007] In order to solve these problems, Patent Document 1 discloses a technology for improving stress relaxation and preventing light leakage by incorporating an acrylic copolymer using an aromatic ring-containing monomer. However, the adhesive using the aromatic ring-containing monomer listed in Patent Document 1 has problems such as white spots occurring in light leakage evaluation and poor optical properties. In addition, the inventors' investigations revealed that if the non-volatile content was 25%, the viscosity would be too high, making coating difficult, and therefore it was not possible to increase the non-volatile content.
[0008] Patent Document 2 discloses a technique for imparting removability by blending a low molecular weight acrylic polymer having a high acid value and a weight average molecular weight of 2 to 100,000 with a high molecular weight acrylic polymer having a weight average molecular weight of 500,000 or more. However, the pressure-sensitive adhesive described in Patent Document 2 has a problem in that the drying conditions for the pressure-sensitive adhesive are limited.
[0009] Patent Document 3 discloses a technique for improving durability and adhesive properties under heated or humid conditions by using a block polymer using two or more monomers. However, the adhesive described in Patent Document 3 has a problem in that the transmittance decreases under heated or humid conditions.
[0010] Patent Document 4 discloses a technology that makes it difficult for depolarization to occur and also provides reworkability and recyclability by using a water-dispersible pressure-sensitive adhesive that contains an acrylic copolymer having a glass transition temperature of -55° C. or more and less than 0° C. and an acrylic copolymer having a glass transition temperature of 0° C. or more and 180° C. or less. However, the pressure-sensitive adhesive described in Patent Document 4 has a problem in that it lacks reworkability after being applied for a long period of time due to various additives used in the pressure-sensitive adhesive.
[0011] Patent Document 5 discloses a technology for suppressing peeling under high temperature and high humidity conditions by constructing an interpenetrating network structure in a cured state using an acrylic copolymer containing hydroxyl groups and alkylene oxide groups and a polyfunctional isocyanate curing agent. However, the adhesive described in Patent Document 5 has a problem in that when left in a high temperature and high humidity environment for a long period of time, the alkylene oxide groups decompose, causing peeling and lifting.
[0012] Also, Patent Document 6 discloses a technology that uses an acrylic copolymer containing hydroxyl and carboxyl groups, a mercapto group-containing silane compound, and alcohol to suppress lifting and peeling of an adhesive sheet when it is placed in a high-temperature and high-humidity environment for a long period of time. However, the adhesive described in Patent Document 6 uses a highly volatile silane compound, so when the adhesive is applied and dried, the silane compound volatilizes, and there is not a sufficient amount of the silane compound remaining in the adhesive layer after application, which causes the problem of lifting and peeling. [Prior art documents] [Patent documents]
[0013] [Patent Document 1] JP 2007-169329 A [Patent Document 2] JP 2010-100710 A [Patent Document 3] JP 2013-82772 A [Patent Document 4] JP 2014-1365 A [Patent Document 5] JP 2014-55299 A [Patent Document 6] JP 2004-59711 A Summary of the Invention [Problem to be solved by the invention]
[0014] The problem to be solved by the present invention is to provide a pressure-sensitive adhesive composition that has excellent low viscosity when adjusted to a predetermined non-volatile content, excellent peelability when used in a pressure-sensitive adhesive sheet, and is unlikely to lift or peel off from an adherend after exposure to a high temperature environment or a high temperature and high humidity environment, and a pressure-sensitive adhesive sheet using the same, in order to solve the above problems.Furthermore, the present invention aims to provide a pressure-sensitive adhesive composition that has extremely low light leakage evaluation when used for fixing a polarizing plate, has good adhesive strength that can maintain high transparency even when exposed to a high temperature and high humidity environment, and does not contaminate an adherend such as glass, and a pressure-sensitive adhesive sheet using the same. [Means for solving the problem]
[0015] The present inventors conducted extensive research to solve the above problems and arrived at the present invention. That is, the present invention relates to a pressure-sensitive adhesive composition comprising an acrylic polymer (A) and a curing agent (B), wherein the acrylic polymer (A) is a copolymer of a monomer mixture comprising the following monomer (a1) and monomer (a2), and satisfies the following formula (1), the content of (a2) is 40 to 95 parts by mass relative to 100 parts by mass of the monomer mixture, the amount of curing agent (B) added is 0.01 to 5 parts by mass relative to 100 parts by mass of the acrylic polymer (A), and the pressure-sensitive adhesive layer comprising the pressure-sensitive adhesive composition has a gel fraction of 55 to 90%. (a1) A (meth)acrylic acid ester monomer having a homopolymer glass transition temperature of 0°C or higher and having no functional group. (a2) 2-octyl (meth)acrylate Equation (1) 1500≦Σ(T 2 ×M A / 100)≦38000 T: Glass transition temperature of homopolymer (a1) (K) M A : Content of (a1) (parts by mass) in 100 parts by mass of monomer mixture
[0016] The present invention also relates to the pressure-sensitive adhesive composition, wherein the curing agent (B) contains an isocyanate-based curing agent.
[0017] The present invention also relates to the pressure-sensitive adhesive composition, further comprising an organosilane (C).
[0018] The present invention also relates to the pressure-sensitive adhesive composition, wherein the content of the monomer (a3) having a carboxy group in 100 parts by mass of the monomer mixture constituting the acrylic polymer (A) is 10 parts by mass or less.
[0019] The present invention also relates to the pressure-sensitive adhesive composition, which is used for fixing a polarizing plate.
[0020] The present invention also relates to a pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition.
[0021] The present invention also relates to a laminate comprising a pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition and a light-transmitting substrate.
[0022] The present invention also relates to a polarizing plate with a pressure-sensitive adhesive layer, comprising a pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition.
[0023] The present invention also relates to a display comprising a pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition, a light-transmitting substrate, a polarizing plate, and an optical element. Effect of the Invention
[0024] The present invention makes it possible to provide a pressure-sensitive adhesive composition which has excellent low viscosity when adjusted to a specified non-volatile content, excellent removability when used in a pressure-sensitive adhesive sheet, and which is unlikely to lift or peel off from an adherend, such as glass or plastics, after exposure to a high-temperature environment or a high-temperature, high-humidity environment, and which is unlikely to cause light leakage. [Brief description of the drawings]
[0025] [Figure 1] 1 is a schematic cross-sectional view partially showing a laminate of the present invention. [Diagram 2] FIG. 1 is a schematic cross-sectional view partially illustrating a display, which is an example of the use of the laminate of the present invention. [Diagram 3] 1 is a schematic cross-sectional view partially illustrating a pressure-sensitive adhesive sheet of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] The pressure-sensitive adhesive composition, pressure-sensitive adhesive sheet, laminate and display of the present invention will be described below, but the present invention is not limited thereto. In this specification, the term "(meth)acrylic acid ester" includes acrylic acid ester and methacrylic acid ester, and the term "(meth)acryloxy group" includes acryloxy group and methacryloxy group. The term "monomer" refers to a monomer having an ethylenically unsaturated group. In addition, in this specification, a numerical range specified by "~" includes the numerical values written before and after "~" as the lower and upper limit ranges. Furthermore, "film" and "sheet" are not distinguished by thickness. In other words, in this specification, a "sheet" includes a thin film-like material, and a "film" includes a thick sheet-like material. Furthermore, the adherend refers to a counterpart to which the pressure-sensitive adhesive layer of the pressure-sensitive adhesive sheet is attached. Unless otherwise noted, the various components appearing in this specification may be used independently as a single type or as a combination of two or more types.
[0027] <<Adhesive composition>> The pressure-sensitive adhesive composition of the present invention contains an acrylic polymer (A) and a curing agent (B).
[0028] <Acrylic polymer (A)> The acrylic polymer (A) is a copolymer of a monomer mixture containing the monomer (a1) and the monomer (a2) described below.
[0029] [Monomer (a1)] The monomer (a1) is a (meth)acrylate monomer having no functional group and having a glass transition temperature of 0° C. or higher as a homopolymer. The glass transition temperature (°C) of homopolymers can be obtained from information from the vendors of various monomers or from the values listed in "Polymer Handbook 3rd Edition" (A WILEY-INTERSCIENCE PUBLICATION, 1989).
[0030] Examples of monomer (a1) include methyl (meth)acrylate, ethyl methacrylate, ter-butyl methacrylate, sec-butyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, isopropyl methacrylate, stearyl (meth)acrylate, isobornyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, and phenyl (meth)acrylate. From the viewpoint of improving cohesive strength and adhesive strength, the monomer (a1) is preferably selected from the group consisting of methyl (meth)acrylate, ethyl methacrylate, isobornyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, and phenyl (meth)acrylate.
[0031] The acrylic polymer (A) satisfies the following formula (1). Equation (1) 1500≦Σ(T 2 ×M A / 100)≦38000 T: Glass transition temperature of homopolymer (a1) (K) M A : Content of (a1) (parts by mass) in 100 parts by mass of monomer mixture By setting the content of monomer (a1) so that the acrylic polymer (A) satisfies formula (1), the cohesive strength of the pressure-sensitive adhesive composition is improved and a tough pressure-sensitive adhesive layer can be obtained, which can suppress lifting and peeling when exposed to a high-temperature atmosphere and also ensure the removability required when re-attaching to an optical component. The lower limit of formula (1) is preferably 3900, and more preferably 7100. The upper limit of formula (1) is preferably 32000, and more preferably 24000.
[0032] [Monomer (a2)] The monomer (a2) is 2-octyl (meth)acrylate. Since the monomer (a2) is available as a biologically derived material, the ratio of biologically derived material can be increased by using the monomer (a2). In addition, the flexibility of the adhesive layer is improved, the adhesion of the adhesive layer to the substrate is further improved, and lifting and peeling can be further suppressed when exposed to a high temperature atmosphere or a high temperature and high humidity atmosphere. Furthermore, by including the monomer (a2), even if the acrylic polymer (A) has a high molecular weight, the viscosity tends to be lower than that of a polymer not containing the monomer (a2) of the same molecular weight, and even if the adhesive composition has a high non-volatile content, the viscosity does not increase too much and the adhesive composition becomes easy to handle.
[0033] The content of monomer (a2) is 40 to 95 parts by mass in 100 parts by mass of the monomer mixture. It is preferably 50 to 95 parts by mass, more preferably 60 to 90 parts by mass, and most preferably 70 to 85 parts by mass. By setting the content of monomer (a2) to 40 to 95 parts by mass, it is possible to suppress an increase in viscosity of the pressure-sensitive adhesive composition, and to achieve both adhesion and durability when exposed to a high-temperature atmosphere or a high-temperature and high-humidity atmosphere.
[0034] The ratio of 2-octyl acrylate in 100% by mass of monomer (a2) is preferably 75% by mass or more, more preferably 85% by mass or more, and most preferably 95% by mass or more. By making it 75% by mass or more, adhesion to various optical members can be ensured, and when a polarizing plate is formed and exposed to a high-temperature atmosphere or a high-temperature and high-humidity atmosphere, lifting and peeling can be further suppressed.
[0035] [Monomer (a3)] The monomer mixture constituting the acrylic polymer (A) may further contain a monomer having a carboxy group as the monomer (a3).
[0036] The content of (a3) is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, even more preferably less than 0.5 parts by mass, and most preferably 0.1 parts by mass or less, per 100 parts by mass of the monomer mixture. By making the content 10 parts by mass or less, the corrosion resistance when the pressure-sensitive adhesive sheet is attached to a transparent electrode can be improved, and lifting and peeling can be further suppressed when the formed polarizing plate is exposed to a high-temperature atmosphere or a high-temperature and high-humidity atmosphere.
[0037] The monomer (a3) having a carboxy group is not limited as long as it has a carboxy group in the molecule, and specific examples thereof include (meth)acrylic acid, p-carboxybenzyl acrylate, β-carboxyethyl acrylate, maleic acid, monoethyl maleic acid, itaconic acid, citraconic acid, and fumaric acid. Of these, (meth)acrylic acid is preferred from the viewpoint of adhesive strength, and acrylic acid is more preferred.
[0038] [Monomer (a4)] The monomer mixture constituting the acrylic polymer (A) may further contain a monomer having a hydroxyl group as the monomer (a4). By containing a monomer having a hydroxyl group, the viscosity increase of the adhesive can be suppressed, and it becomes easier to achieve both adhesion and durability when exposed to a high temperature atmosphere or a high temperature and high humidity atmosphere. The monomer having a hydroxyl group (a4) is not limited as long as it is a monomer having a hydroxyl group in the molecule, and specifically includes 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, etc., and these may be used alone or in combination of two or more. The average number of carbon atoms in the alkyl chain of the hydroxyl group-containing monomer (a4) is preferably 2.5 or more, and more preferably 3 or more. This improves the reactivity with the curing agent and imparts cohesive strength to the adhesive layer, making it easier to prevent lifting and peeling when a polarizing plate is formed and exposed to a high-temperature atmosphere or a high-temperature, high-humidity atmosphere.
[0039] The content of the hydroxyl group-containing monomer (a4) is preferably 0.1 to 20 parts by mass, more preferably 0.1 to 5 parts by mass, and most preferably 0.2 to 1.5 parts by mass, in 100 parts by mass of the monomer mixture. By setting the content of the hydroxyl group-containing monomer to 0.1 to 20 parts by mass, it is possible to suppress an increase in viscosity of the pressure-sensitive adhesive composition, and it becomes easier to achieve both adhesion to optical members, removability, and durability when exposed to a high-temperature atmosphere or a high-temperature, high-humidity atmosphere.
[0040] [Other monomers] The monomer mixture constituting the acrylic polymer (A) may contain other monomers as optional components in addition to the above (a1) to (a4). Examples include (meth)acrylic acid ester monomers having no functional group and having a homopolymer glass transition temperature (Tg) of less than 0°C (ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, n-amyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, dodecyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, dodecyl (meth)acrylate, octadecyl (meth)acrylate), alkoxy-based (meth)acrylic acid esters such as methoxyethyl acrylate, vinyl-based monomers such as vinyl acetate and styrene, monomers having a glycidyl group such as glycidyl (meth)acrylate, and monomers containing a nitrogen atom.
[0041] Examples of the nitrogen atom-containing monomer include N-vinyl lactams, cyclic amides such as vinylpyridine, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, vinyloxazole, vinylmorpholine, and (meth)acryloylmorpholine, N-vinyl carboxylic acid amides such as N-vinylformamide and N-vinylacetamide, acrylonitrile, acrylamide, and N,N-dimethylacrylamide. N-vinyl lactams are monomers having a cyclic lactam ring, and examples thereof include N-vinyl-2-pyrrolidone, N-vinyl-2-piperidone, N-vinyl-ε-caprolactam, and compounds having a structure in which one or more of these hydrogen atoms are substituted with a substituent. Examples of the substituent include an alkyl group having 1 to 20 carbon atoms, an alkyl group having 2 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, a carboxy ester group having 3 to 20 carbon atoms, and an amino group having 1 to 20 carbon atoms, but do not include acidic groups such as a hydroxy group, a carboxylic acid (salt) group, a sulfonic acid (salt) group, or a hypophosphorous acid (salt) group. Among these, cyclic amides and N-vinyl lactams are preferred, and N-vinyl lactams are more preferred.
[0042] The content of other monomers is preferably 25 parts by mass or less, more preferably 20 parts by mass or less, even more preferably 15 parts by mass or less, especially preferably 10 parts by mass or less, and most preferably 5 parts by mass or less, per 100 parts by mass of the monomer mixture.
[0043] (Production of acrylic polymer (A)) The acrylic polymer (A) can be produced by polymerizing the above-mentioned monomer mixture. The polymerization can be carried out by known polymerization methods such as solution polymerization, bulk polymerization, emulsion polymerization, and suspension polymerization, but solution polymerization is preferred. The solvent used in the solution polymerization is preferably, for example, acetone, methyl acetate, ethyl acetate, toluene, xylene, anisole, methyl ethyl ketone, cyclohexanone, etc. The polymerization temperature is preferably a boiling point reaction at 60 to 120°C. The polymerization time is preferably about 5 to 12 hours.
[0044] The polymerization initiator used in the polymerization is preferably a radical polymerization initiator, and the radical polymerization initiator is generally a peroxide or an azo compound. Examples of the peroxide include dialkyl peroxides such as di-t-butyl peroxide, dicumyl peroxide, t-butylcumyl peroxide, α,α'-bis(t-butylperoxy-m-isopropyl)benzene, and 2,5-di(t-butylperoxy)hexyne-3; Peroxyesters such as t-butyl peroxybenzoate, t-butyl peroxyacetate, and 2,5-dimethyl-2,5-di(benzoylperoxy)hexane; ketone peroxides such as cyclohexanone peroxide, 3,3,5-trimethylcyclohexanone peroxide, and methylcyclohexanone peroxide; Peroxyketals such as 2,2-bis(4,4-di-t-butylperoxycyclohexyl)propane, 1,1-bis(t-butylperoxy)3,3,5-trimethylcyclohexane, 1,1-bis(t-butylperoxy)cyclohexane, and n-butyl-4,4-bis(t-butylperoxy)valerate; Hydroperoxides such as cumene hydroperoxide, diisopropylbenzene hydroperoxide, and 2,5-dimethylcyclohexane-2,5-dihydroperoxide; Diacyl peroxides such as benzoyl peroxide, decanoyl peroxide, lauroyl peroxide, and 2,4-dichlorobenzoyl peroxide; Examples include peroxydicarbonates such as bis(t-butylcyclohexyl) peroxydicarbonate.
[0045] Examples of the azo compound include 2,2'-azobisbutyronitrile such as 2,2'-azobisisobutyronitrile (abbreviation: AIBN) and 2,2'-azobis(2-methylbutyronitrile); 2,2'-azobisvaleronitrile such as 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) and 2,2'-azobis(2,4-dimethylvaleronitrile); 2,2'-azobispropionitriles such as 2,2'-azobis(2-hydroxymethylpropionitrile); Examples include 1,1'-azobis-1-alkanenitriles such as 1,1'-azobis(cyclohexane-1-carbonitrile).
[0046] The polymerization initiator is preferably used in an amount of 0.01 to 10 parts by mass, more preferably 0.1 to 2 parts by mass, based on 100 parts by mass of the monomer mixture.
[0047] (Weight average molecular weight (Mw)) The weight-average molecular weight of the acrylic polymer (A) is preferably 800,000 to 1,800,000, more preferably 1,000,000 to 1,700,000. By setting the weight-average molecular weight within the above range, it becomes easier to ensure adhesion to optical members, removability, and durability when exposed to a high-temperature atmosphere. The weight-average molecular weight is a value calculated in terms of polystyrene measured by gel permeation chromatography (GPC).
[0048] <Hardening agent (B)> The pressure-sensitive adhesive composition of the present invention contains 0.01 to 5 parts by mass of a curing agent (B) based on 100 parts by mass of the acrylic polymer (A). The curing agent to be blended in the pressure-sensitive adhesive composition is preferably one that reacts with the carboxy group of the monomer (a3) and / or the hydroxy group of the monomer (a4) by heat or the like to form a bond. Blending the curing agent in the above ratio improves the cohesive strength of the pressure-sensitive adhesive layer, and can achieve both adhesion to optical members, removability, and durability when exposed to a high-temperature atmosphere or a high-temperature, high-humidity atmosphere. The blending amount of the curing agent (B) is preferably 0.1 to 2 parts by mass based on 100 parts by mass of the acrylic polymer (A).
[0049] The curing agent can be appropriately selected from known curing agents such as epoxy-based curing agents, isocyanate-based curing agents, oxazoline-based curing agents, aziridine-based curing agents, carbodiimide-based curing agents, metal chelate-based curing agents, and melamine-based curing agents, taking into consideration the reactivity with the functional groups of the polymer in the pressure-sensitive adhesive composition. From the viewpoint of removability, it is preferable to include an isocyanate-based curing agent.
[0050] Examples of epoxy curing agents include N,N,N',N'-tetraglycidyl-m-xylylenediamine, tetraglycidyl-3,3'-diaminodiphenyl sulfone, tetraglycidyldiaminodiphenylmethane, 1,3-bis(N,N'-diglycidylaminomethyl)cyclohexane, N,N,N',N'-tetraglycidylaminophenylmethane (the above are examples of tetrafunctional epoxy compounds), glycerin diglycidyl ether, 1,6-hexanediol diglycidyl ether, and the like, from which one or more can be selected as appropriate.
[0051] The isocyanate-based curing agent is an isocyanate having two or more isocyanate groups. For example, the isocyanate is preferably an aromatic polyisocyanate, an aliphatic polyisocyanate, an araliphatic polyisocyanate, an alicyclic polyisocyanate, and their biuret, nurate, and adduct, and more preferably an aliphatic polyisocyanate, an alicyclic polyisocyanate, and their biuret, nurate, and adduct from the viewpoint of yellowing resistance.
[0052] The biuret form is a self-condensation product having a biuret bond formed by self-condensation of an isocyanate monomer, for example, a biuret form of hexamethylene diisocyanate.
[0053] The nurate form is a trimer of an isocyanate monomer, such as a trimer of hexamethylene diisocyanate, a trimer of isophorone diisocyanate, or a trimer of tolylene diisocyanate.
[0054] The adduct is a bifunctional or higher isocyanate compound obtained by reacting an isocyanate monomer with a bifunctional or higher low-molecular active hydrogen-containing compound. Examples of the adduct include a compound obtained by reacting trimethylolpropane with hexamethylene diisocyanate, a compound obtained by reacting trimethylolpropane with tolylene diisocyanate, a compound obtained by reacting trimethylolpropane with xylylene diisocyanate, a compound obtained by reacting trimethylolpropane with isophorone diisocyanate, and a compound obtained by reacting 1,6-hexanediol with hexamethylene diisocyanate.
[0055] The isocyanate compound is preferably a trifunctional isocyanate compound from the viewpoint of forming a sufficient crosslinked structure. The isocyanate compound is more preferably an adduct which is a reaction product between an isocyanate monomer and a trifunctional low molecular weight active hydrogen-containing compound, and a nurate. The isocyanate compound is preferably a trimethylolpropane adduct of hexamethylene diisocyanate, a nurate of hexamethylene diisocyanate, a trimethylolpropane adduct of tolylene diisocyanate, a nurate of tolylene diisocyanate, a trimethylolpropane adduct of isophorone diisocyanate, or a nurate of isophorone diisocyanate, and more preferably a trimethylolpropane adduct of hexamethylene diisocyanate, a trimethylolpropane adduct of tolylene diisocyanate, or a trimethylolpropane adduct of isophorone diisocyanate.
[0056] The oxazoline-based curing agent has two or more oxazoline groups in the molecule, and may be a low molecular weight compound or a polymer. Examples of the low molecular weight compound oxazoline-based curing agent include 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, 2-isopropenyl-5-ethyl-2-oxazoline, 2,2'-bis-(2-oxazoline), 2,2'-methylene-bis-(2-oxazoline), 2,2'-ethylene-bis-(2-oxazoline), 2,2'-trimethylene-bis-(2-oxazoline), and 2,2'-tetramethylene-bis-(2-oxazoline). , 2,2'-hexamethylene-bis-(2-oxazoline), 2,2'-octamethylene-bis-(2-oxazoline), 2,2'-ethylene-bis-(4,4'-dimethyl-2-oxazoline), 2,2'-p-phenylene-bis-(2-oxazoline), 2,2'-m-phenylene-bis-(2-oxazoline), 2,2'-m-phenylene-bis-(4,4'-dimethyl-2-oxazoline), 2,2'-(1,3-phenylene)-bis-(2-oxazoline), bis-(2-oxazolinylcyclohexane)sulfide, bis-(2-oxazolinylnorbornane)sulfide, etc. Examples of oxazoline-based curing agents for polymers include polymers that contain addition-polymerizable oxazoline as an essential component. Examples of the addition-polymerizable oxazoline include 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, 2-isopropenyl-5-methyl-2-oxazoline, and 2-isopropenyl-5-ethyl-2-oxazoline.
[0057] Examples of the aziridine-based curing agent include N,N'-diphenylmethane-4,4'-bis(1-aziridinecarboxite), tris-2,4,6-(1-aziridinyl)-1,3,5-triazine, and 4,4'-bis(ethyleneiminocarbonylamino)diphenylmethane.
[0058] The carbodiimide compound is preferably a high molecular weight polycarbodiimide produced by decarboxylation condensation of a diisocyanate compound in the presence of a carbodiimide catalyst. The commercially available high molecular weight polycarbodiimide is preferably the Carbodilite series from Nisshinbo Industries, Ltd. Among them, Carbodilite V-03, 07, and 09 are preferred because of their excellent compatibility with organic solvents.
[0059] The metal chelate is preferably a coordination compound of a polyvalent metal such as aluminum, iron, copper, zinc, tin, titanium, nickel, antimony, magnesium, vanadium, chromium, or zirconium with acetylacetone or ethyl acetoacetate. Examples of the metal chelate include aluminum ethyl acetoacetate diisopropylate, aluminum trisacetylacetonate, aluminum bisethyl acetoacetate monoacetylacetonate, and aluminum alkyl acetoacetate diisopropylate.
[0060] Representative examples of the melamine-based hardener include fully alkyl-etherified melamine resins, methylol group-type melamine resins, and imino group-type melamine resins partially containing imino groups.
[0061] <Organosilane (C)> The pressure-sensitive adhesive composition of the present invention preferably contains an organic silane (C). By containing the organic silane (C), it becomes easier to achieve both adhesion to optical members, removability, and durability when exposed to a high-temperature atmosphere or a high-temperature, high-humidity atmosphere. The organic silane (C) is preferably contained in an amount of 0.001 to 1 part by mass, more preferably 0.005 to 0.8 parts by mass, per 100 parts by mass of the acrylic polymer (A). By setting the amount within the above range, it becomes easier to achieve both adhesion to optical members, removability, and durability when exposed to a high-temperature atmosphere or a high-temperature, high-humidity atmosphere.
[0062] Examples of the organic silane (C) include an alkoxysilane compound having a (meth)acryloxy group, an alkoxysilane compound having a vinyl group, an alkoxysilane compound having an amino group, an alkoxysilane compound having a mercapto group, or an alkoxysilane compound having an epoxy group. Of these, an alkoxysilane compound having an epoxy group is preferred. Specific examples of commercially available products include alkoxysilane compounds having an epoxy group such as KBM-403 (3-glycidoxypropyltrimethoxysilane), KBE-403 (3-glycidoxypropyltriethoxysilane), and KBM-303 (2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane) (all manufactured by Shin-Etsu Chemical Co., Ltd.), and other organic amines such as BYK-325N (polyether-modified polymethylalkylsiloxane) (manufactured by BYK Japan KK).
[0063] The pressure-sensitive adhesive composition of the present invention may contain other compounds, such as chlorinated polyolefins, antistatic agents, silicone oils, and tackifier resins, within the scope of the invention.
[0064] (Chlorinated polyolefin) Examples of chlorinated polyolefins include chlorinated polypropylene, acid-modified chlorinated polypropylene, acrylic-modified chlorinated polypropylene, chlorinated polyethylene, and chlorinated ethylene-vinyl acetate copolymer. From the viewpoints of good compatibility with acrylic polymers and the like and effective reduction in polarity, chlorinated polypropylene and chlorinated ethylene-vinyl acetate copolymer are preferred. Specific examples of commercially available products include Superchlorine 390S (chlorinated polypropylene, chlorine content 36%) and Superchlorine BX (chlorinated EVA, chlorine content 18%) (both manufactured by Nippon Paper Industries Co., Ltd.).
[0065] (Antistatic agent) Examples of antistatic agents include inorganic salts, ionic liquids, ionic solids, surfactants, etc. Among these, ionic liquids are preferred. Note that "ionic liquids" are also called room temperature molten salts, and exhibit liquid properties at 25°C.
[0066] Examples of inorganic salts include sodium chloride, potassium chloride, lithium chloride, lithium perchlorate, ammonium chloride, potassium chlorate, aluminum chloride, copper chloride, ferrous chloride, ferric chloride, ammonium sulfate, potassium nitrate, sodium nitrate, sodium carbonate, and sodium thiocyanate.
[0067] The ionic liquid is a salt of a cation and an anion, and the cation is preferably, for example, an imidazolium ion, a pyridinium ion, an ammonium ion, or the like. Examples of ionic liquids containing imidazolium ions include 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1,3-dimethylimidazolium bis(trifluoromethylsulfonyl)imide, and 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide.
[0068] Examples of ionic liquids containing pyridinium ions include 1-methylpyridinium bis(trifluoromethylsulfonyl)imide, 1-butylpyridinium bis(trifluoromethylsulfonyl)imide, 1-hexylpyridinium bis(trifluoromethylsulfonyl)imide, 1-octylpyridinium bis(trifluoromethylsulfonyl)imide, 1-hexyl-4-methylpyridinium bis(trifluoromethylsulfonyl)imide, 1-hexyl-4-methylpyridinium hexafluorophosphate, 1-octyl-4-methylpyridinium bis(trifluoromethylsulfonyl)imide, 1-octyl-4-methylpyridinium bis(fluorosulfonyl)imide, 1-methylpyridinium bis(perfluoroethylsulfonyl)imide, and 1-methylpyridinium bis(perfluorobutylsulfonyl)imide.
[0069] Examples of ionic liquids containing ammonium ions include trimethylheptylammonium bis(trifluoromethanesulfonyl)imide, N,N-diethyl-N-methyl-N-propylammonium bis(trifluoromethanesulfonyl)imide, N,N-diethyl-N-methyl-N-pentylammonium bis(trifluoromethanesulfonyl)imide, N,N-diethyl-N-methyl-N-heptylammonium bis(trifluoromethanesulfonyl)imide, and tri-n-butylmethylammonium bistrifluoromethanesulfonimide.
[0070] In addition, known ionic liquids in which the cation is a pyrrolidinium ion, a phosphonium ion, a sulfonium ion, or the like can be appropriately used.
[0071] Like ionic liquids, ionic solids are salts of cations and anions, but exhibit solid properties at normal pressure and 25° C. Preferred cations are, for example, alkali metal ions, phosphonium ions, pyridinium ions, ammonium ions, and the like.
[0072] Examples of the ionic solid containing an alkali metal ion include lithium bisfluorosulfonylimide, lithium bistrifluoromethylsulfonylimide, lithium bispentafluoroethylsulfonylimide, lithium bisheptafluoropropylsulfonylimide, lithium bisnonanefluorobutylsulfonylimide, sodium bisfluorosulfonylimide, sodium bistrifluoromethylsulfonylimide, sodium bispentafluoroethylsulfonylimide, sodium bisheptafluoropropylsulfonylimide, sodium bisnonanefluorobutylsulfonylimide, potassium bisfluorosulfonylimide, potassium bistrifluoromethylsulfonylimide, potassium bispentafluoroethylsulfonylimide, potassium bisheptafluoropropylsulfonylimide, and potassium bisnonanefluorobutylsulfonylimide.
[0073] Examples of the ionic solid containing a phosphonium ion include tetrabutyl phosphonium bisfluorosulfonylimide, tetrabutyl phosphonium bistrifluoromethylsulfonylimide, tetrabutyl phosphonium bispentafluoroethylsulfonylimide, tetrabutyl phosphonium bisheptafluoropropylsulfonylimide, tetrabutyl phosphonium bisnonanefluorobutylsulfonylimide, tributyl hexadecyl phosphonium bisfluorosulfonylimide, tributyl hexadecyl phosphonium bistrifluoromethylsulfonylimide, tributyl hexadecyl phosphonium bispentafluoroethylsulfonylimide, tributyl hexadecyl phosphonium bisheptafluoropropylsulfonylimide, tributyl hexadecyl phosphonium bisnonanefluorobutylsulfonylimide, tetraoctyl phosphonium bisfluorosulfonylimide, tetraoctyl phosphonium bistrifluoromethylsulfonylimide, tetraoctyl phosphonium bispentafluoroethylsulfonylimide, tetraoctyl phosphonium bisheptafluoropropylsulfonylimide, and tetraoctyl phosphonium bisnonanefluorobutylsulfonylimide.
[0074] Examples of the ionic solid containing a pyridinium ion include 1-hexadecyl-4-methylpyridinium bisfluorosulfonylimide, 1-hexadecyl-4-methylpyridinium bistrifluoromethylsulfonylimide, 1-hexadecyl-4-methylpyridinium bispentafluoroethylsulfonylimide, 1-hexadecyl-4-methylpyridinium bisheptafluoropropylsulfonylimide, and 1-hexadecyl-4-methylpyridinium bisnonanefluorobutylsulfonylimide.
[0075] Examples of the ionic solid containing ammonium ions include tributylmethyl bistrifluoromethylsulfonylimide, tributylmethyl bispentafluoroethylsulfonylimide, tributylmethyl bisheptafluoropropylsulfonylimide, tributylmethyl bisnonanefluorobutylsulfonylimide, octyltributyl bistrifluoromethylsulfonylimide, octyltributyl bispentafluoroethylsulfonylimide, octyltributyl bisheptafluoropropylsulfonylimide, octyltributyl bisnonanefluorobutylsulfonylimide, tetrabutyl bisfluorosulfonylimide, tetrabutyl bistrifluoromethylsulfonylimide, tetrabutyl bispentafluoroethylsulfonylimide, tetrabutyl bisheptafluoropropylsulfonylimide, and tetrabutyl bisnonanefluorobutylsulfonylimide. In addition, known ionic solids in which the cation is a pyrrolidinium ion, an imidazolium ion, a sulfonium ion, or the like can be appropriately used.
[0076] Surfactants can be classified into nonionic, anionic, cationic, and amphoteric types.
[0077] Examples of nonionic surfactants include glycerin fatty acid esters, polyoxyalkylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene alkylamines, polyoxyethylene alkylamine fatty acid esters, fatty acid diethanolamides, polyether ester amide types, ethylene oxide-epichlorohydrin types, and polyether ester types.
[0078] Examples of anionic surfactants (excluding ionic liquids and ionic solids) include alkylsulfonates, alkylbenzenesulfonates, alkylphosphates, and polystyrenesulfonate types. Examples of the cationic surfactant include tetraalkylammonium salts, trialkylbenzylammonium salts, and quaternary ammonium base-containing acrylate polymers.
[0079] Examples of amphoteric surfactants include amino acid type amphoteric surfactants such as alkyl betaines, alkyl imidazolium betaines, and higher alkyl amino propionates, and betaine type amphoteric surfactants such as higher alkyl dimethyl betaines and higher alkyl dihydroxyethyl betaines.
[0080] The antistatic agents may be used alone or in combination of two or more.
[0081] When an antistatic agent is added, the blending amount is preferably 0.01 to 3 parts by mass, more preferably 0.03 to 2 parts by mass, and even more preferably 0.06 to 1 part by mass, relative to 100 parts by mass of the acrylic polymer (A). When an appropriate amount of an antistatic agent is blended, the removability is less likely to decrease when exposed to a high-temperature and high-humidity atmosphere, and the yield during the production of the pressure-sensitive adhesive sheet is improved.
[0082] (Silicone oil) Examples of silicone oils include dimethyl silicone oil, methyl phenyl silicone oil, methyl hydrogen silicone oil, side-chain type polyether-modified silicone oil, aralkyl-modified silicone oil, fluoroalkyl-modified silicone oil, long-chain alkyl-modified silicone oil, higher fatty acid ester-modified silicone oil, higher fatty acid amide-modified silicone oil, polyether-long-chain alkyl-modified silicone oil-aralkyl-modified silicone oil, phenyl-modified silicone oil, both-end type polyether-modified silicone oil, polyether-methoxy-modified silicone oil, and the like.
[0083] When silicone oil is added, the blending amount is preferably 1 to 10 parts by mass, more preferably 1 to 5 parts by mass, per 100 parts by mass of the acrylic polymer (A). Blending an appropriate amount of silicone oil makes it difficult for the removability to decrease when exposed to a high-temperature and high-humidity atmosphere, and improves the yield when producing the pressure-sensitive adhesive sheet.
[0084] (tackifier resin) Examples of tackifying resins include aliphatic petroleum resins, aromatic petroleum resins, synthetic hydrocarbon resins, terpene resins, rosin resins (rosin, polymerized rosin, hydrogenated rosin, and their esters with glycerin, pentaerythritol, etc., resin acid dimers, etc.), and acrylic resins.
[0085] When a tackifier resin is added, the blending amount is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, even more preferably 10 parts by mass or less, and most preferably substantially none, relative to 100 parts by mass of the acrylic polymer (A). By setting the amount of the tackifier resin added within such a range, it is possible to prevent a decrease in adhesive strength caused by softening of the adhesive layer even in a high-temperature atmosphere, and further to ensure removability required when reattaching to an optical member.
[0086] Examples of aliphatic petroleum resins include Quinton B170 manufactured by Zeon Corporation; examples of aromatic petroleum resins include Nippon Oil Neopolymer L-90 manufactured by JXTG; examples of aliphatic / aromatic petroleum resins include FTR6100 manufactured by Mitsui Chemicals, Inc.; and examples of rosin derivatives include SylvatacRE85 manufactured by Arizona Chemical Company and Superester A-75 manufactured by Arakawa Chemical Industries, Ltd.
[0087] Examples of synthetic hydrocarbon resins include aliphatic petroleum resins, aromatic petroleum resins, aliphatic / aromatic petroleum resins, hydrogenated petroleum resins, coumarone-indene resins, and phenol resins.
[0088] Examples of terpene resins include α-pinene resins, β-pinene resins, dipentene resins, aromatic modified terpene resins, hydrogenated terpene resins, terpene phenol resins, acid modified terpene resins, styrenated terpene resins, and styrene-aliphatic hydrocarbon copolymer resins.
[0089] Examples of rosin-based resins include rosin ester, polymerized rosin, hydrogenated rosin, disproportionated rosin, maleic acid modified rosin, fumaric acid modified rosin, rosin phenolic resin, and natural rosin.
[0090] The viscosity of the pressure-sensitive adhesive composition is not particularly limited, but it is preferable that the viscosity when adjusted to a predetermined non-volatile content according to the weight average molecular weight of the acrylic polymer (A) contained is 7000 mPa·s or less. Specifically, when the weight average molecular weight of the acrylic polymer (A) is 1.5 million or more, the viscosity at 20.0±0.5% nonvolatile content is preferably less than 7000 mPa·s, when the weight average molecular weight of the acrylic polymer (A) is 1 million or more and less than 1.5 million, the viscosity at 25.0±0.5% nonvolatile content is preferably less than 7000 mPa·s, and when the weight average molecular weight of the acrylic polymer (A) is less than 1 million, the viscosity at 30.0±0.5% nonvolatile content is preferably less than 7000 mPa·s. Such a viscosity makes handling during coating easier, and makes it easier to obtain a defect-free adhesive layer.
[0091] <Adhesive layer> The pressure-sensitive adhesive layer of the present invention has a gel fraction of 55 to 90% by mass. 60 to 80% by mass is more preferable. When the gel fraction is 55% by mass or more, the cohesive strength of the pressure-sensitive adhesive composition is improved, a strong pressure-sensitive adhesive layer is obtained, and the pressure-sensitive adhesive layer is less likely to protrude from the edge when folded. When the gel fraction is 55% by mass or more, the cohesive strength of the pressure-sensitive adhesive is improved and a strong pressure-sensitive adhesive layer is obtained, so that lifting and peeling can be suppressed when exposed to a high-temperature atmosphere, and further, removability required when reattaching to an optical member can be ensured. When the gel fraction is 90% by mass or less, a flexible pressure-sensitive adhesive layer is easily obtained, and the adhesion of the pressure-sensitive adhesive layer to the substrate (hereinafter referred to as substrate adhesion) is further improved, and lifting and peeling can be further suppressed when exposed to a high-temperature atmosphere or a high-temperature and high-humidity atmosphere. In general, the gel fraction of a polymer is equal to the degree of crosslinking, and the more crosslinked parts in the polymer, the higher the gel fraction. The gel fraction (amount of crosslinked structure introduced) can be adjusted to a desired range by the method of introducing the crosslinked structure, the type and amount of the crosslinking agent, etc. The method for measuring the gel fraction will be described in detail in the Examples.
[0092] Adhesive sheet The pressure-sensitive adhesive sheet comprises a pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition of the present invention.
[0093] The pressure-sensitive adhesive sheet of the present invention preferably has a configuration in which a release film is attached to at least one side of the pressure-sensitive adhesive layer. Specifically, the pressure-sensitive adhesive sheet has a configuration in which release films are formed on both sides of the pressure-sensitive adhesive layer, or a release film is formed on one side of the pressure-sensitive adhesive layer and a light-transmitting substrate is provided on the other side of the pressure-sensitive adhesive, and the pressure-sensitive adhesive layer is formed from the pressure-sensitive adhesive composition of the present invention.
[0094] <Release film> The release film is not particularly limited, but a transparent plastic substrate can be suitably used. Examples of the material of the transparent plastic substrate include polyester such as polyethylene terephthalate (PET), acrylic resin such as polymethyl methacrylate (PMMA), polycarbonate, triacetyl cellulose, polysulfone, polyarylate, polycycloolefin, and other plastic materials. The plastic materials can be used alone or in combination of two or more kinds.
[0095] As the release film, among the above-mentioned transparent plastic substrates, a transparent plastic substrate having excellent heat resistance, i.e., a transparent plastic substrate in which deformation is suppressed or prevented under severe conditions such as high temperature, high temperature and high humidity, etc. As the transparent plastic substrate, a PET film or sheet is particularly suitable.
[0096] The thickness of the transparent plastic substrate is not particularly limited, and is, for example, preferably from 10 to 200 μm, and more preferably from 25 to 150 μm.
[0097] The pressure-sensitive adhesive sheet of the present invention has adhesion to optical members, removability, and durability when exposed to a high-temperature atmosphere or a high-temperature and high-humidity atmosphere, so it is suitable as a pressure-sensitive adhesive for forming optical display members such as display devices such as LCDs and OLEDs and input devices such as touch panels, and for bonding these members together. However, since it has excellent durability in a high-temperature and high-humidity environment when attached to a polarizing plate, it is preferable that at least one side of the pressure-sensitive adhesive layer is attached to a polarizing plate. The optical members are not particularly limited, and include PET films, COP films, polarizing plates, retardation plates, elliptical polarizing plates, optical compensation films, brightness improvement films, infrared / electromagnetic wave cut films, front anti-reflection films, surface protection films, films having an ITO (indium tin oxide) layer, films having a zinc oxide (ZnO) layer, films obtained by coating or printing metal nanoparticles, films obtained by coating or printing a dispersion containing carbon nanotubes, films obtained by coating or printing a dispersion containing graphene, films obtained by coating or printing a dispersion containing conductive polymers, metal plates formed of SUS, metal meshes, and further laminates thereof.
[0098] In coating the adhesive composition, a suitable liquid medium can be added to adjust the viscosity.Specific examples of the solvent include hydrocarbon solvents such as toluene, xylene, hexane, and heptane; ester solvents such as ethyl acetate and butyl acetate; ketone solvents such as acetone and methyl ethyl ketone; halogenated hydrocarbon solvents such as dichloromethane and chloroform; ether solvents such as diethyl ether, methoxytoluene, and dioxane, and other hydrocarbon solvents.However, water and alcohol should be used with caution because they may cause reaction inhibition between the acrylic polymer (A) and the isocyanate curing agent (B).
[0099] The coating method is not particularly limited, and various coating methods can be used, such as a Mayer bar, applicator, brush, spray, roller, gravure coater, die coater, lip coater, comma coater, knife coater, reverse coater, spin coater, etc. In addition, the drying and curing method is not particularly limited, and examples thereof include hot air drying, infrared rays, reduced pressure methods, and active energy rays, but hot air or steam heating at 60 to 180°C is preferred from the viewpoint of outgassing resistance.
[0100] The thickness of the pressure-sensitive adhesive layer is preferably 2 to 1000 μm, more preferably 5 to 500 μm, further preferably 10 to 100 μm, and most preferably 20 to 50 μm. The pressure-sensitive adhesive layer may be in the form of a single layer or a laminate of two or more layers.
[0101] <Laminate> The laminate includes a light-transmitting substrate and a pressure-sensitive adhesive layer, and the pressure-sensitive adhesive layer is formed using the pressure-sensitive adhesive sheet of the present invention. Specifically, for example, the release film is peeled off from the pressure-sensitive adhesive sheet of the present invention, and the pressure-sensitive adhesive layer is attached to the light-transmitting substrate to form the laminate.
[0102] <Light transparent base material> A transparent plastic substrate is used as the light-transmitting substrate. Examples of the material of such a light-transmitting substrate include acrylic resins such as polyethylene terephthalate (PET), polyethylene naphthalate, and polymethyl methacrylate (PMMA), and plastic materials such as polycarbonate (PC), polycycloolefin (COP), polyimide, polyphenylene ether, polysulfone, polyethersulfone, polystyrene, and polypropylene. In particular, PET film or PC is preferred, and PC is even more preferred in terms of durability. The plastic materials can be used alone or in combination of two or more kinds. The light-transmitting substrate may be subjected to an appropriate surface treatment, for example, a physical treatment such as a corona discharge treatment or a plasma treatment, or a chemical treatment such as an undercoat treatment.
[0103] <Polarizing plate with adhesive layer> The polarizing plate with a pressure-sensitive adhesive layer includes a polarizing plate and a pressure-sensitive adhesive layer, and the pressure-sensitive adhesive layer is formed by using the pressure-sensitive adhesive sheet of the present invention. Specifically, for example, the polarizing plate with a pressure-sensitive adhesive layer can be formed by peeling the release film from the pressure-sensitive adhesive sheet of the present invention and attaching the pressure-sensitive adhesive layer to the polarizing plate.
[0104] An example of a schematic cross-sectional view partially showing the laminate of the present invention is shown in Fig. 1. In Fig. 1, 3 is a light-transmitting substrate (cover panel), 1 is a pressure-sensitive adhesive layer, and 4 is a polarizing plate.
[0105] In the laminate shown in FIG. 1, a light-transmitting substrate (cover panel) is attached to a polarizing plate via a pressure-sensitive adhesive layer.
[0106] <Production of Laminate and Polarizing Plate with Pressure-Sensitive Adhesive> The laminate and the polarizing plate with adhesive can be manufactured, for example, by peeling off the release film from an adhesive sheet having a release film on both sides of the adhesive layer, and attaching the adhesive layer to a light-transmitting substrate or a polarizing plate. Alternatively, the laminate can be manufactured by peeling off the release film from an adhesive sheet having a release film on one side of the adhesive layer and a light-transmitting substrate on the other side, and attaching the adhesive layer to a light-transmitting substrate or a polarizing plate. Furthermore, the laminate can be manufactured by directly forming an adhesive layer on a light-transmitting substrate, and then attaching an adhesive layer provided on an adherend or another adhesive sheet to the adhesive layer.
[0107] "display" The display of the present invention comprises a light-transmitting substrate, a pressure-sensitive adhesive layer, a polarizing plate, and an optical element, and thus has excellent visibility. The optical element is not particularly limited, and examples thereof include a liquid crystal element and an organic EL element.
[0108] Fig. 2 shows an example of a schematic cross-sectional view partially illustrating a display, which is an example of the use of the pressure-sensitive adhesive sheet of the present invention. In Fig. 2, 3 is a light-transmitting substrate (cover panel), 1 is a pressure-sensitive adhesive layer 1, 4 is a polarizing plate, 5 is a pressure-sensitive adhesive layer 2, 6 is a barrier layer such as silicon nitride, 7 is an organic EL layer, 8 is a support such as polyimide, and 9 is an organic EL cell. Note that the configuration of the display is not limited to that shown in Fig. 2.
[0109] In the display shown in Fig. 2, a light-transmitting substrate (cover panel) is attached to a polarizing plate via the pressure-sensitive adhesive layer of the present invention (pressure-sensitive adhesive layer 1), and is further attached to an organic EL cell via a pressure-sensitive adhesive layer for polarizing plate (pressure-sensitive adhesive layer 2). Thus, the pressure-sensitive adhesive sheet of the present invention can be used in a form in which a transparent pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition is attached to a light-transmitting substrate (cover panel) and a polarizing plate, and the laminate is further attached to an organic EL cell via a pressure-sensitive adhesive layer for polarizing plate. For example, in FIG. 2, the pressure-sensitive adhesive composition of the present invention can be used for both pressure-sensitive adhesive layer 1 and pressure-sensitive adhesive layer 2 . In general, when comparing the pressure-sensitive adhesive layer 1 and the pressure-sensitive adhesive layer 2, the pressure-sensitive adhesive layer 1 is required to have higher quality, and since the pressure-sensitive adhesive composition of the present invention has good adhesion and bonding to the substrate, it is preferably used for the pressure-sensitive adhesive layer 1. In this case, the pressure-sensitive adhesive for forming the pressure-sensitive adhesive layer 2 may be the pressure-sensitive adhesive composition of the present invention or a conventionally known pressure-sensitive adhesive.
[0110] There are no particular limitations on the uses of the displays, but examples include OLED televisions, OLED smartphones, OLED tablets, and OLED smartwatches. EXAMPLES
[0111] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the examples, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass". The blending amounts in the tables are parts by mass, and the amounts other than the solvent are calculated as non-volatile contents. The blanks in the tables indicate that no blending was performed. The method for measuring the weight average molecular weight of the acrylic polymer is as follows.
[0112] <Measurement of weight average molecular weight (Mw)> Weight average molecular weight (Mw) was measured by gel permeation chromatography (GPC). Shimadzu Corporation's GPC device: LC-GPC system "Prominence" was used. Tosoh Corporation's TSKgel α-M was used as the column, and two columns were connected in series. N,N-dimethylformamide (DMF) was used as the eluent, and measurements were performed at 40°C. Mw was determined by conversion using polystyrene with a known Mw as the standard substance. Based on the results of the weight average molecular weight measurements, the resins were classified into H, M, and L categories according to the following criteria. H: Molecular weight 1.5 million or more M: Molecular weight 1 million to less than 1.5 million L: Molecular weight less than 1 million
[0113] <Production example of acrylic polymer> (Acrylic polymer (A-1)) Using a reaction apparatus equipped with a stirrer, reflux condenser, nitrogen inlet tube, thermometer, and dropping tube, 10 parts of methyl acrylate (MA, Tg = 8 ° C.) as monomer (a1), 88.5 parts of 2-octyl acrylate (2OA) as monomer (a2), 1.5 parts of 4-hydroxybutyl acrylate (4HBA) as monomer (a4), and 110 parts of methyl acetate as a solvent were charged into a reaction vessel, and polymerized at 70 ° C. for 5 hours under a nitrogen atmosphere, during which the viscosity was appropriately adjusted by dropping ethyl acetate. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution (A-1) with a non-volatile content of 30.0 ± 0.5%. The weight average molecular weight (Mw) of the obtained acrylic polymer is shown in Table 1.
[0114] (Acrylic polymers (A-2 to A-34, A'-1 to A'-4)) Acrylic polymers (A-2 to A-33, A'-1 to A'-4) were synthesized in the same manner as for the production of acrylic polymer (A-1), except that the compositions and amounts (parts by mass) were changed to those shown in Tables 1 to 4. The weight average molecular weights of the obtained acrylic polymers are shown in Tables 1 to 3.
[0115] [Table 1]
[0116] [Table 2]
[0117] [Table 3]
[0118] The abbreviations are as follows: [Monomer (a1)] MA: Methyl acrylate (alkyl group carbon number 1, Tg = 8°C) BzA: benzyl acrylate (Tg=6°C) CHA: Cyclohexyl acrylate (Tg=15°C) IBXA: Isobornyl acrylate (Tg=97℃) MMA: Methyl methacrylate (alkyl group carbon number 1, Tg = 105°C) IBXMA: Isobornyl methacrylate (Tg=180℃) [Monomer (a2)] 2OA: 2-octyl acrylate 2OMA: 2-octyl methacrylate [Monomer (a3)] AA: Acrylic acid [Monomer (a4)] HEA: Hydroxyethyl acrylate 4HBA: 4-Hydroxybutyl acrylate [Other monomers] 2EHA: 2-ethylhexyl acrylate (alkyl group carbon number: 8, Tg = -70°C) DDA: normal dodecyl acrylate (alkyl group carbon number: 12, Tg = -23°C)
[0119] The materials used in the examples and comparative examples are listed below. <Hardening agent B> [Isocyanate-based hardener] B-1: ("NP-1200", manufactured by Mitsui Chemicals, burette form of hexamethylene diisocyanate) B-2: ("D-172N", Mitsui Chemicals, Inc., hexamethylene diisocyanate nurate) B-3: ("D-160N", Mitsui Chemicals, Inc., hexamethylene diisocyanate modified with trimethylolpropane) B-4: ("Desmodur 2565", manufactured by Covestro, nurate form of isophorone diisocyanate) B-5: ("Coronate L", Tosoh Corporation, trimethylolpropane modified toluene diisocyanate) [Other hardeners] B-6: Zirconium tetraacetylacetonate: ("Orgatics ZC-700", Matsumoto Fine Chemical Co., Ltd.) B-7: N,N,N',N'-Tetraglycidyl-m-xylylenediamine (TETRAD-X)
[0120] <Organosilane (C)> KBE-403: (3-glycidoxypropyltriethoxysilane, manufactured by Shin-Etsu Chemical Co., Ltd.) KBM-303: ([2-(3,4-epoxycyclohexyl)ethyl]trimethoxysilane, manufactured by Shin-Etsu Chemical Co., Ltd.)
[0121] <Tackifier resin> SE10: (Haritac SE10, hydrogenated rosin, manufactured by Harima Chemicals Co., Ltd.) FTR6100: (FTR6100, aliphatic / aromatic petroleum resin, manufactured by Mitsui Chemicals, Inc.) A-100: (Super Ester A-100, rosin-based resin, manufactured by Arakawa Chemical Industries, Ltd.) T130: (YS Polystar T130, terpene phenol resin, manufactured by Yasuhara Chemical Co., Ltd.)
[0122] <Example 1> 100 parts of acrylic polymer (A-1) was mixed with 0.4 parts of B-1 ("NP-1200", Mitsui Chemicals, Inc., biuret form of hexamethylene diisocyanate) as curing agent (B) and 0.1 parts of KBE-403 (3-glycidoxypropyltriethoxysilane, Shin-Etsu Chemical Co., Ltd.) as organosilane (C), and diluted with ethyl acetate to a nonvolatile content of 25.0±0.5%, to obtain a pressure-sensitive adhesive composition. The obtained adhesive composition was applied to a 38 μm thick polyethylene terephthalate release sheet (Therapeel MF: manufactured by Toray Film Processing Co., Ltd.) using a comma coater so that the thickness after drying would be 25 μm, and dried at 100° C. for 2 minutes to obtain an adhesive sheet. Next, one side of a 100 μm thick polyethylene terephthalate film (hereinafter referred to as PET film, product name: A-4300, manufactured by Toyobo Co., Ltd.) was attached to the adhesive surface of this adhesive sheet to obtain a laminate having a configuration of "release sheet / adhesive layer / cycloolefin film". Next, the obtained laminate was aged for one week under conditions of a temperature of 25° C. and a relative humidity of 55%, to obtain a laminate (hereinafter referred to as laminate A). In addition, instead of the PET film, a polarizing plate (layer structure: triacetyl cellulose film / polyvinyl alcohol film / polymethyl methacrylate film) was used and laminated so that the adhesive layer and the polymethyl methacrylate film surface of the polarizing plate were in contact with each other, to obtain a polarizing plate with adhesive having a structure of "peeling sheet / adhesive layer / polarizing plate". Next, the obtained polarizing plate with adhesive was aged for one week under conditions of a temperature of 25°C and a relative humidity of 55%. This was named Laminate B.
[0123] <Examples 2 to 51 and Comparative Examples 1 to 6> As shown in Table 4, the types and amounts of the acrylic polymer, curing agent and organosilane were changed, and according to the weight average molecular weight category of the acrylic polymer, if it was H, it was diluted with ethyl acetate so that the non-volatile content was 20.0±0.5%, if it was M, it was diluted with ethyl acetate so that the non-volatile content was 25.0±0.5%, and if it was L, it was not diluted, and the same procedure as in Example 1 was used to obtain a pressure-sensitive adhesive composition, a pressure-sensitive adhesive sheet laminate A and a laminate B, respectively.
[0124] [Gel fraction measurement method] A sample for measuring the gel fraction of 30 mm x 100 mm was cut out from the pressure-sensitive adhesive sheet obtained above, and the release sheet was peeled off to obtain a free film of the pressure-sensitive adhesive layer. The gel fraction of the pressure-sensitive adhesive layer was calculated as the mass fraction (unit: mass%) of the insoluble components after the pressure-sensitive adhesive layer was immersed in ethyl acetate at 50°C for 1 day relative to the pressure-sensitive adhesive layer before immersion, as represented by the following formula 1. (Formula 1) Gel fraction (mass%) = ((XY) / X) x 100 X = mass of adhesive layer before immersion (g) Y = mass of adhesive layer after immersion (g)
[0125] [Table 4]
[0126] {Physical properties and evaluation of pressure-sensitive adhesive composition and laminate} The adhesive composition of the present invention was evaluated for its low viscosity, and the adhesion of the laminate (to glass, acrylic plate, ITO / PET), heat resistance, moist heat resistance, corrosion resistance, light leakage, and removability by the following methods. The results are shown in Table 5.
[0127] <Low viscosity> The viscosity of the pressure-sensitive adhesive compositions of Examples 1 to 46 and Comparative Examples 1 to 6 was measured using a Brookfield viscometer (rotor No. 3, rotation speed 12 rpm). Low viscosity was evaluated based on the following criteria. [Evaluation Criteria] ◎: Viscosity is less than 7000mPa·s (excellent) ○: Viscosity is 7000 mPa·s or more but less than 8000 mPa·s (good) △: Viscosity is 8000 mPa·s or more but less than 9000 mPa·s (fairly good) ▲: Viscosity is 9000 mPa·s or more and less than 10000 mPa·s (usable) ×: Viscosity is 10,000 mPa·s or more (not suitable for use)
[0128] <Adhesiveness> The laminate A obtained above was prepared to a size of 25 mm wide x 100 mm long to prepare a test laminate A. The release sheet of the test laminate A was peeled off, and the adhesive layer was attached to a glass plate in an atmosphere of 23°C and 50% relative humidity, and pressed with a roll in accordance with JIS Z-0237. After 24 hours from pressing, the adhesive strength (peel angle 180°, peel speed 300 mm / min; unit N / 25 mm width) was measured with a universal tensile tester. Separately, the adhesive strength was measured in the same manner as above, except that the adherend was replaced from the glass plate to an acrylic plate and an ITO / PET film. The ITO / PET film was a PET film with indium tin oxide vapor-deposited on it, and a test adhesive sheet was attached to the ITO vapor-deposited surface. The adhesion was evaluated based on the adhesive strength according to the following criteria. [Evaluation Criteria] ◎: Adhesive strength is 5.0N / 25mm or more (Excellent) ○: Adhesive strength is 3.0N / 25mm or more and less than 5.0N / 25mm. (Good) △: Adhesive strength is 2.0N / 25mm or more and less than 3.0N / 25mm. (fairly good) ▲: Adhesive strength is 1.0N / 25mm or more and less than 2.0N / 25mm. (Usable) ×: Adhesive strength is less than 1.0N / 25mm. (Poor)
[0129] <Heat resistance and moist heat resistance evaluation 1> The laminate A obtained above was cut into a size of 930 mm wide and 523 mm long (equivalent to 42 inches). Next, the release sheet was peeled off from the cut laminate A, and the laminate was attached to an ITO sputtered glass plate (80Ω: manufactured by Nippon Sheet Glass Co., Ltd.) using a laminator. Next, the glass plate to which the laminate A was attached was held in an autoclave at 50°C and 5 atm for 20 minutes to bring each member into close contact, thereby obtaining a measurement sample. The heat resistance of this measurement sample was evaluated as an evaluation of resistance in a high-temperature atmosphere. That is, the measurement sample was left at 105°C for 1000 hours, and then visually observed for the presence or absence of foaming, lifting, and peeling. The test samples were also evaluated for their resistance to high temperature and high humidity in a moist heat environment. The test samples were left at 85°C and 85% relative humidity for 500 hours, and then visually observed for the presence or absence of foaming, lifting, or peeling. The heat resistance and moist heat resistance were both evaluated based on the following criteria. [Evaluation Criteria] ◎: No foaming, lifting or peeling was observed (Excellent) ○: Any of the following is observed: foaming, lifting, or peeling of 0.5 mm or less (good). △: Any of the following is observed: foaming, lifting, or peeling exceeding 0.5 mm and not exceeding 1 mm (fairly good). ▲: Any of the following is observed: foaming, lifting, or peeling exceeding 1 mm and not exceeding 1.5 mm (usable). ×: Either foaming, lifting or peeling is observed over the entire surface (unusable)
[0130] <Corrosion resistance> A PET film (IPF-05H125: manufactured by Gunze Co., Ltd.) having an ITO transparent conductive film with a thickness of 5 μm was cut to a width of 40 mm and a length of 100 mm, and attached to an ITO transparent conductive film with a width of 40 mm and a length of 160 mm by peeling off the release sheet from the laminate A. Next, this laminate was held in an autoclave at 50° C. and 5 atm for 20 minutes to bond each member together, thereby obtaining a measurement sample having a layered structure of PET film / adhesive layer / ITO film. Electrodes were connected to both ends of the measurement sample, and the initial electrical resistance value was measured. The measurement sample was then left to stand for 1000 hours at 85°C and 85% relative humidity, and the electrical resistance value after aging was measured in the same manner as above. The corrosion resistance was evaluated based on the following criteria. The electrical resistance value was measured using Laresta-GP MCP-T600 (manufactured by Mitsubishi Chemical Corporation). Electrical resistance increase rate = ((electrical resistance value after aging - initial electrical resistance value) / initial electrical resistance value) [Evaluation Criteria] ◎: The electrical resistance increase rate is less than 0.5 (Excellent) ○: The electrical resistance increase rate is 0.5 or more and less than 1.0 (good). △: The electrical resistance increase rate is 1.0 or more and less than 1.5. (fairly good) ▲: Electrical resistance increase rate is 1.5 or more and less than 2.0. (Can be used) ×: The electrical resistance increase rate is 2.0 or more (unusable).
[0131] <Heat resistance and moist heat resistance evaluation 2> The laminate B obtained above was cut into a size of 930 mm wide and 523 mm long (equivalent to 42 inches). Next, the release sheet was peeled off from the cut laminate B, and the laminate was attached to an ITO sputtered glass plate (80Ω: manufactured by Nippon Sheet Glass Co., Ltd.) using a laminator. Next, the glass plate to which the laminate B was attached was held in an autoclave at 50°C and 5 atm for 20 minutes to adhere each member to each other, thereby obtaining a measurement sample. The heat resistance of this measurement sample was evaluated as a resistance evaluation in a high-temperature atmosphere. That is, the measurement sample was left at 105°C for 1000 hours, and then visually observed for the presence or absence of foaming, lifting, and peeling. The test samples were also evaluated for their resistance to high temperature and humidity in an atmosphere of high humidity and humidity. The test samples were left at 85°C and 95% relative humidity for 1000 hours, and then visually observed for the presence or absence of foaming, lifting, or peeling. The heat resistance and the heat and humidity resistance were both evaluated based on the following criteria. [Evaluation Criteria] ◎: No foaming, lifting or peeling was observed (Excellent) ○: Any of the following is observed: foaming, lifting, or peeling of 0.5 mm or less (good). △: Any of the following is observed: foaming, lifting, or peeling exceeding 0.5 mm and not exceeding 1 mm (fairly good). ▲: Any of the following is observed: foaming, lifting, or peeling exceeding 1 mm and not exceeding 1.5 mm (usable). ×: Either foaming, lifting or peeling is observed all over the surface (unusable).
[0132] <Light leakage> The laminate B obtained above was cut into a size of 930 mm wide and 523 mm long (equivalent to 42 inches). Next, the release sheet was peeled off from the cut laminate B, and two sheets of the laminate B were attached to both sides of an ITO sputtered glass plate (80Ω: manufactured by Nippon Sheet Glass Co., Ltd.) using a laminator so that the absorption axes of the polarizing plates were perpendicular to each other, to obtain a pressure-bonded product. Next, the pressure-bonded product was held in an autoclave at 50°C and 5 atm for 20 minutes to adhere each member to each other, thereby obtaining a measurement sample. This measurement sample was left at 105°C for 1000 hours, and then the light leakage when light was transmitted through the polarizing plate was visually observed. The light leakage was evaluated based on the following criteria. [Evaluation Criteria] ⊚: No white spots are observed (Excellent) ○: One or two white spots are observed (good). △: 3 to 5 white spots are observed (fairly good) ▲: 6 to 10 white spots are observed. (Usable) ×: 11 or more white spots are observed (unusable).
[0133] <Removability> The laminate B obtained above was cut into a size of 100 mm wide and 100 mm long. Next, the release sheet was peeled off from the cut laminate B and attached to an ITO sputtered glass plate (80Ω: manufactured by Nippon Sheet Glass Co., Ltd.) using a laminator. Next, the members were held in an autoclave at 50°C and 5 atm for 20 minutes to adhere to each other, thereby obtaining a measurement sample. After leaving the measurement sample at 105°C for 7 days, a peel test was performed in which the sample was pulled in a 180° direction at a speed of 300 mm / min using a tensile tester ("Tensilon" manufactured by Orientec Co., Ltd.) in an environment of 23°C and relative humidity of 50%. Next, the cloudiness of the glass surface after peeling was visually observed. The above evaluation was performed on 5 samples per type of laminate, and the evaluation was based on the following criteria. [Evaluation Criteria] ◎: No adhesive residue or cloudiness was observed in any of the five samples (Excellent). ○: Of the five samples, only one sample had glue residue or cloudiness of 5% or less of the measured area (good). △: Of the five samples, two samples had glue residue or cloudiness of 5% or less of the measured area. (Fairly good) ▲: Of the five samples, three samples had glue residue or cloudiness of less than 5% of the measured area. (Usable) ×: Of the five samples, at least four samples had glue residue of 5% or less of the measured area, or at least one sample had glue residue or cloudiness of more than 5%. (Not for use)
[0134] [Table 5]
[0135] As shown in Table 5, the pressure-sensitive adhesive composition of the present invention achieved excellent results in terms of low viscosity, adhesion (glass, acrylic plate, ITO / PET), heat resistance and moist heat resistance evaluation, corrosion resistance, light leakage, and removability. On the other hand, the pressure-sensitive adhesive composition of the comparative example did not satisfy all of the following: low viscosity, adhesion (glass, acrylic plate, ITO / PET), heat resistance and moist heat resistance evaluation, corrosion resistance, light leakage, and removability. From these results, it can be said that the pressure-sensitive adhesive composition of the present invention can be suitably used for bonding optical members. [Explanation of symbols]
[0136] The symbols in Figures 1, 2 and 3 are explained below. 1 Adhesive layer 1 2 Release film 3 Film substrate (cover panel) 4. Polarizing Plate 5 Adhesive layer 2 6 Barrier Layer 7 Organic EL layer 8 Support 9 Organic EL Cell
Claims
1. A pressure-sensitive adhesive composition comprising an acrylic polymer (A) and a curing agent (B), The acrylic polymer (A) is a copolymer of a monomer mixture containing the following monomer (a1) and monomer (a2): The following formula (1) is satisfied: The content of (a2) is 40 to 95 parts by mass based on 100 parts by mass of the monomer mixture, The amount of the curing agent (B) added is 0.01 to 5 parts by mass based on 100 parts by mass of the acrylic polymer (A), A pressure-sensitive adhesive composition, characterized in that a pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition has a gel fraction of 55 to 90%. (a1) A (meth)acrylic acid ester monomer having no functional group and having a glass transition temperature of 0° C. or higher as a homopolymer. (a2) 2-octyl (meth)acrylate Formula (1) 1500≦Σ(T 2 ×M A / 100)≦38000 T: glass transition temperature (K) of the homopolymer (a1) M A : Content (parts by mass) of (a1) in 100 parts by mass of monomer mixture
2. 2. The pressure-sensitive adhesive composition according to claim 1, wherein the curing agent (B) comprises an isocyanate-based curing agent.
3. The pressure-sensitive adhesive composition according to claim 1, further comprising an organosilane (C).
4. 2. The pressure-sensitive adhesive composition according to claim 1, wherein the content of the monomer (a3) having a carboxy group in 100 parts by mass of the monomer mixture constituting the acrylic polymer (A) is 10 parts by mass or less.
5. The pressure-sensitive adhesive composition according to any one of claims 1 to 4, which is used for fixing a polarizing plate.
6. A pressure-sensitive adhesive sheet comprising a pressure-sensitive adhesive layer comprising the pressure-sensitive adhesive composition according to any one of claims 1 to 4.
7. A laminate comprising a pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition according to any one of claims 1 to 4 and a light-transmitting substrate.
8. A polarizing plate with a pressure-sensitive adhesive layer, comprising a pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition according to claim 5.
9. A display comprising a pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition according to any one of claims 1 to 4, a light-transmitting substrate, a polarizing plate, and an optical element.
Citation Information
Patent Citations
2-Octyl (meth)acrylate adhesive composition
JP2011516690A
Pressure-sensitive adhesive composition
JP2023538015A
Adhesive tape
WO2024143341A1
Pressure-sensitive adhesive composition and pressure-sensitive adhesive sheet
JP2004059711A
Adhesive composition for optical use and adhesive sheet
JP2007169329A
Cited By
Semiconductor device and semiconductor storage device
DE102025137718A1
Semiconductor device and semiconductor memory device
EP4811959A1
Composition and adhesive sheet
JP7928590B1